Isolated traumatic brain injury: Routine intubation for Glasgow Coma Scale 7 or 8 may be harmful!. Issue 5 (18th May 2021) - Jakob, Dominik A.; Lewis, Meghan; Benjamin, Elizabeth R.; Demetriades, Demetrios
Abstract : INTRODUCTION: Despite strong recommendations, there is no direct evidence supporting routine intubation of trauma patients with Glasgow Coma Scale (GCS) score of 7 or 8. We hypothesized that routine intubation may not be beneficial in isolated blunt head injury. METHODS: A retrospective Trauma Quality Improvement Program study, including adult blunt trauma patients with GCS score of 7 or 8 and isolated head injury, was performed. Epidemiological and clinical characteristics, neurosurgical procedures, timing of intubation, and outcome variables were collected. The study population was stratified by the intubation procedure: immediate intubation (≤1 hour of admission), delayed intubation (>1 hour of admission), and no intubation. Multivariable regression analysis was used to determine risk factors for mortality and complications, as well as factors predictive of the decision to intubate. RESULTS: Of 2, 727 patients with GCS score of 7 or 8 and isolated blunt head trauma, 1, 866 patients (68.4%) were intubated within 1 hour of admission (immediate intubation), 223 (8.2%) had an intubation >1 hour of admission (delayed intubation), and 638 patients (23.4%) were not intubated at all. After correcting for age, sex, overall comorbidities, tachycardia, GCS, alcohol, illegal drug use, and head injury severity, immediate intubation was independently associated with higher mortality (odds ratio, 1.79; 95% confidence interval, 1.31–2.44; p < 0.001) and more overall complications (odds ratio, 2.46; 95% confidence interval, 1.62–3.73; p < 0.001). Increasing head Abbreviated Injury Scale (AIS) score, GCS score of 7, and tachycardia were identified as independent clinical factors associated with the decision to intubate. A policy of intubating all isolated blunt head injury patients 45 years or younger with head AIS score of 5 and GCS score of 7 would have improved intubation management, with seven immediate instead of delayed intubations and only three potentially unnecessary intubations. CONCLUSION: In patients with GCS score of 7 or 8 and isolated head injury, immediate intubation was associated with higher mortality and more overall complications. Intubation management could have been improved by intubating all patients younger than 45 years with head AIS score of 5 and a GCS score of 7 on admission. LEVEL OF EVIDENCE: Therapeutic, level III.